2016
DOI: 10.1097/mop.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurodevelopmental benefits of breastfeeding

Abstract: Pediatricians play a critical role in educating and counseling families about infant nutrition and feeding. Along with the many positive short-term medical effects that breastfeeding confers, physicians should be aware of the growing body of research suggesting that there are also significant long-term neurodevelopmental benefits of breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 54 publications
4
96
1
4
Order By: Relevance
“…Breastfeeding is a dynamic, interactive, and bidirectional social behavior and “not simply a meal at the breast” [Kaye & Wells, ; Raju, ]. There are numerous benefits of breastfeeding for the child, such as providing key nutrients for physical and neurologic development, protecting from infections, and decreasing the risk for food allergies, asthma, and cardiovascular diseases [Bar, Milanaik, & Adesman, ; Brahm & Valdes, ]. The American Academy of Pediatrics (AAP) recommends exclusive breastfeeding for the first 6 months of life and continuation of breastfeeding for at least a year, or as mutually desired by the mother and the child [American Academy of Pediatrics, ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is a dynamic, interactive, and bidirectional social behavior and “not simply a meal at the breast” [Kaye & Wells, ; Raju, ]. There are numerous benefits of breastfeeding for the child, such as providing key nutrients for physical and neurologic development, protecting from infections, and decreasing the risk for food allergies, asthma, and cardiovascular diseases [Bar, Milanaik, & Adesman, ; Brahm & Valdes, ]. The American Academy of Pediatrics (AAP) recommends exclusive breastfeeding for the first 6 months of life and continuation of breastfeeding for at least a year, or as mutually desired by the mother and the child [American Academy of Pediatrics, ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the long‐term neurodevelopmental benefits of breastfeeding are still being studied. Some authors have observed positive results; however, others have not confirmed the neurodevelopmental benefits or the effects were small (Bar et al, ; Der, Batty, & Deary, ; von Stumm & Plomin, ; Yang et al, ). These differences could be explained by associated variables, such as the education and ethnicity of mothers, and family poverty, among others (Boucher et al, ; Der et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, breastfeeding has been associated with higher intelligence quotient during both periods (Prado & Dewey, 2014), and with fewer autistic traits (Boucher et al, 2017) and conduct disorders (Rochat et al, 2016). However, most of the literature is limited to people of European descent (Bar, Milanaik, & Adesman, 2016), and only a few studies have considered the relationship with complementary feeding (Prado & Dewey, 2014). Thus, the current study aimed to analyze the relationship between feeding during infancy and cognitive performance in schoolchildren of rural indigenous communities in Riobamba, Ecuador.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, WHO and United Nations Children's Fund (UNICEF) recommend that all mothers should breastfeed their children exclusively for the first 6 months and thereafter continue to breastfeed for as long as the mother and child desire, with appropriate and sufficient weaning food included after 6 months of life (2,3). EBF is associated with multiple benefits ranging from cognitive to physical development over the life course of the infant (6)(7)(8). This practice is essential for good child health in the short term given its associated lower incidence and severity of diarrhea, reduced respiratory tract infections and lower incidence of allergic diseases among children at-risk (9,10).…”
Section: Introductionmentioning
confidence: 99%